The Potential Effects of Dielectric Barrier Discharge Plasma on the Extraction Efficiency of Bioactive Compounds in Radix Paeoniae Alba - Jin, Tao; Zhou, Zhenghua; Zhou, Jian; Ouyang, Wenchong; Wu, Zhengwei (Frontiers in Nutrition, 2021)
Radix paeoniae alba (RPA) is a kind of herbal medicine of traditional Chinese medicine (TCM) that is widely used for the treatment of liver diseases and rheumatoid arthritis in clinical practice. As a result of the low extraction efficiency of RPA by the conventional method, many patients are given high dosages. In this study, four exposure doses of dielectric barrier discharge (DBD) plasma (0, 60, 120, and 180 s) were applied to modify the extraction efficiency of paeoniflorin, benzoylpaeoniflorin, tannic acid, gallic acid, 2′-hydroxy-4′-methoxyacetophenone, and polysaccharide in RPA. Finally, the application of plasma for 180 s exhibited a 24.6% and 12.0% (p < 0.001) increase of tannic acid and polysaccharide contents, however, a 2.1% (p < 0.05) and 5.4% (p < 0.001) reduction of paeoniflorin and gallic acid composition, respectively, and no significant difference (p > 0.05) in results obtained from benzoylpaeoniflorin and 2′-hydroxy-4′-methoxyacetophenone contents. Our results of scanning electron microscopy (SEM), automatic specific surface area and pore analyzer, Fourier transform infrared spectroscopy (FTIR), X-ray photoelectron spectroscopy (XPS), and thermal gravimetric analysis (TGA) indicated that DBD plasma can etch the surface and undergo graft polymerization by reactive species thereby changing the water/oil holding capacity and eventually changing the extraction efficiency of bioactive compounds in RPA. Overall, our observations provide a scientific foundation for modifying the extraction efficiency of bioactive ingredients related to the pharmacological activities of RPA.